The role of dietary magnesium deficiency in inflammatory hypertension - Pitzer Mutchler, Ashley; Huynh, Linh; Patel, Ritam; Lam, Tracey; Bain, Daniel; Jamison, Sydney; Kirabo, Annet; Ray, Evan C. (Frontiers in Physiology, 2023)
Nearly 30% of adults consume less than the estimated average daily requirement of magnesium (Mg2+), and commonly used medications, such as diuretics, promote Mg2+ deficiency. Higher serum Mg2+ levels, increased dietary Mg2+ in-take, and Mg2+ supplementation are each associated with lower blood pressure, suggesting that Mg2+-deficiency contributes to the pathogenesis of hypertension. Antigen-presenting cells, such as monocytes and dendritic cells, are well-known to be involved in the pathogenesis of hypertension. In these cells, processes implicated as necessary for increased blood pressure include activation of the NLRP3 inflammasome, IL-1β production, and oxidative modification of fatty acids such as arachidonic acid, forming isolevuglandins (IsoLGs). We hypothesized that increased blood pressure in response to dietary Mg2+-depletion leads to increased NLRP3, IL-1β, and IsoLG production in antigen presenting cells. We found that a Mg2+-depleted diet (0.01% Mg2+ diet) increased blood pressure in mice compared to mice fed a 0.08% Mg2+ diet. Mg2+-depleted mice did not exhibit an increase in total body fluid, as measured by quantitative magnetic resonance. Plasma IL-1β concentrations were increased (0.13 ± 0.02 pg/mL vs. 0.04 ± 0.02 pg/mL). Using flow cytometry, we observed increased NLRP3 and IL-1β expression in antigen-presenting cells from spleen, kidney, and aorta. We also observed increased IsoLG production in antigen-presenting cells from these organs. Primary culture of CD11c+ dendritic cells confirmed that low extracellular Mg2+ exerts a direct effect on these cells, stimulating IL-1β and IL-18 production. The present findings show that NLRP3 inflammasome activation and IsoLG-adduct formation are stimulated when dietary Mg2+ is depleted. Interventions and increased dietary Mg2+ consumption may prove beneficial in decreasing the prevalence of hypertension and cardiovascular disease.